Supplementation of Casein Tablets of Goat Milk Yogurt on Dioxin-exposed Broiler Chickens Feed Consumption - Wicaksono, Agung; Oktanella, Yudit; Widodo, Edwin (Journal of Food and Life Sciences, 2021)
Combustion process in industry resulted in harmful free radical compounds such as Dioxin / TCDD (2,3,7,8- tetrachlorodibenzo-p-dioxin). The aim of the this experiment was to determine the therapeutic effect of casein in goat milk yogurt on chickens exposed to dioxins. Parameters used in this experiment were feed consumption and body weight. This research was designed with 18 male COBB strain broiler chickens aged 21 days. They were divided into three groups: (1) the negative group without any treatment, (2) the positive group by giving feed with dioxin 50ng / kg feed in corn oil solvent, (3) ) the therapy group was given feed with dioxin 50ng / kg feed in corn oil solvent in the morning and 750 mg / kg BW / day of yougurt casein goat milk in the afternoon. Both feed and casein were given orally for 21 days with each group having six replications. The samples were measured every day including weight gain and chicken feed consumption. The data were analyzed quantitatively using the One Way Analysis of Variance (ANOVA) test with a confidence level of 95%. The provision of goat milk yogurt casein tablets as a therapy for broiler chickens that were given dioxin-containing feed had a significant increase on chicken body weight, but insignificant on feed consumption.